2016
DOI: 10.3390/ma9010040
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of the Process Capabilities of Hydroforging

Abstract: Hydroforging is a hybrid forming operation whereby a thick tube is formed to a desired geometry by combining forging and hydroforming principles. Through this process hollow structures with high strength-to-weight ratio can be produced for applications in power transmission systems and other structural components that demands high strength-to-weight ratio. In this process, a thick tube is deformed by pressurized fluid contained within the tube using a multi-purpose punch assembly, which is also used to feed tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Thin-walled machine parts with a wall thickness lower than 2 mm can be formed from sheet metal plates [9] or thin-walled tubes. To this end, the hydroforming method is most often used, in which the process stability is ensured by high-pressure liquids [10]. An alternative to liquids is the use of flexible media [11,12], e.g., those made of elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…Thin-walled machine parts with a wall thickness lower than 2 mm can be formed from sheet metal plates [9] or thin-walled tubes. To this end, the hydroforming method is most often used, in which the process stability is ensured by high-pressure liquids [10]. An alternative to liquids is the use of flexible media [11,12], e.g., those made of elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the precrash of the tube increased H(w min ) almost to the top of the dome (Figure 5b). Thickness (mm) w ∈ (w1; w1 + 1.25) w ∈ (w2; w2 + 2.00) 1 (precrash max 4 mm).…”
Section: Fem Modelmentioning
confidence: 99%
“…In fact, the current production process consists of a multiphase process that mainly consists in tube preforming, cutting, welding of the third branch and beads grinding. In order to enhance the product, the company chose to investigate the possibility of replacing the current manufacturing process with Tube Hydroforming (THF) [1]. In THF, a blank tube is placed in hollow dies that are shaped as the desired geometry of the part.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations